The Impact Of Compensation And Work Environment On Employee Performance At A Cable Company - Zainal Musthafa; Ade Suhara; Sevty Auliani (JTI: Jurnal Teknik Industri, 2024)
This study aims to analyze the effect of compensation and work environment on employee performance at CV Bintang Timur Mandiri. Using a quantitative approach with a sample of 40 employees, this study found that compensation significantly positively affects employee performance, with a t-value of 2.685, more significant than the t table of 1.685. On the other hand, the work environment does not significantly affect employee performance, with a t-value of -0.176, which is smaller than the t table of 1.685. However, compensation and work environment simultaneously affect employee performance with a calculated F value of 10.501, greater than the F table 3.25. The results of this study indicate the importance of providing fair compensation, creating a comfortable work environment, increasing motivation through training and recognition of achievements, and managing human resources well. These steps will contribute to the productivity and positive image of the company. Keywords: Compensation, Work Environment, Employee Performance